2008
DOI: 10.1118/1.2919560
|View full text |Cite
|
Sign up to set email alerts
|

MLC quality assurance using EPID: A fitting technique with subpixel precision

Abstract: Amorphous silicon based electronic portal imaging devices (EPIDs) have been shown to be a good alternative to radiographic film for routine quality assurance (QA) of multileaf collimator (MLC) positioning accuracy. In this work, we present a method of acquiring an EPID image of a traditional strip-test image using analytical fits of the interleaf and leaf abutment image signatures. After exposure, the EPID image pixel values are divided by an open field image to remove EPID response and radiation field variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…Our study has demonstrated the need for accuracy in both the modelling of the MLC system in the TPS and in calibration as well as quality assurance (QA) of the MLC in order to minimize systematic errors of IMRT treatment delivery. Various MLC QA for IMRT techniques have been described in the literature [12,16,25,26] and recommendations for modelling of MLC have been proposed by the AAPM Task Group No. 50 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our study has demonstrated the need for accuracy in both the modelling of the MLC system in the TPS and in calibration as well as quality assurance (QA) of the MLC in order to minimize systematic errors of IMRT treatment delivery. Various MLC QA for IMRT techniques have been described in the literature [12,16,25,26] and recommendations for modelling of MLC have been proposed by the AAPM Task Group No. 50 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent development of tools utilizing EPID devices allow for subpixel precision to detect changes in discrete locations of an acquired image. 69,70 As treatment planning parametrization seeks a global value for leaf transmission, it is important that the leaf body, side, and end characteristics do not change over time, the most vulnerable being the leaf side rigidity due to leaf inderdigitation, as it may affect interleaf leakage, hence the close attention needed. Leaf position repeatability, MLC spoke shot, and coincidence of light field and x-ray field all are tests intended to check the alignment of the MLCs.…”
Section: Iid3 Mlcmentioning
confidence: 99%
“…Since pixels of kV and MV images are about 0.4 mm or larger and CBCT slices are 1 mm thick, small BBs cannot provide one‐tenths‐mm accuracy. However, it has been demonstrated that with computer aid the position of regular‐shaped objects that extend over many pixels can be found with accuracy substantially better than pixel size 9 , 12 . The center of a sphere having a radius of about 10 times the pixel dimensions, e.g., can be determined with accuracy of one‐tenth pixel size (13) .…”
Section: Methodsmentioning
confidence: 99%